PELATIHAN PENYUSUNAN SILABUS DAN RPP BAHASA INGGRIS TERINTEGRASI PENDIDIKAN KARAKTER BAGI GURU-GURU BAHASA INGGRIS TINGKAT SEKOLAH DASAR DI KECAMATAN MRANGGEN KABUPATEN DEMAK - Ngasbun egar; Rahmawati Sukmaningrum; Siti Musarokah; Faiza Hawa (Universitas PGRI Semarang, 2012)
Demoralization occured in school life. Teachers as the person incharge of the students?óÔé¼Ôäó education in school must find the way out to demolish the demoralization. Character Education needs to be developed in school to maintain students?óÔé¼Ôäó behaviour. Character Building is important to be developed in the learning process. The development of Character Building is integrated into subject matters in elementary schools. Teachers should be involved in the character education for students. In running the process of learning, instructional materials are needed. Syllabus and lesson plan are parts of the instructional materials. Teachers are not only responsible for educating students in school but also responsible for building students?óÔé¼Ôäó characters through the material they deliver. Character Buildings are integrated in the syllabus and lesson plan in order that the students can apply the moral values from the material they learn in their daily lifes. The syllabus and lesson plan improvement with all the potency can be used for supporting the effectivity of character education implementation which is becoming the prior attention. Teachers should know more about students personality and what students need in the learning process. Teachers can improve their skills in making syllabus and lesson plans based character education by joining this workshop. Teachers need to be ?óÔé¼?ôan up-date?óÔé¼?Ø person in giving materials and delivering the moral values to build the students?óÔé¼Ôäó character. Through the program of repetition drills and monitoring, teachers can learn more about syllabus based character education to fulfill the students?óÔé¼Ôäó need. Syllabus based character education has to be used for imprasing the character education in order for gaining teachers?óÔé¼Ôäó and students?óÔé¼Ôäó creativity.Key words: Syllabus, Character Buildings.